2018
DOI: 10.1530/eje-17-0946
|View full text |Cite
|
Sign up to set email alerts
|

GENETICS IN ENDOCRINOLOGY: The expanding genetic horizon of primary aldosteronism

Abstract: 2 AbstractAldosterone is the main mineralocorticoid hormone in humans and plays a key role in maintaining water and electrolyte homeostasis. Primary aldosteronism (PA), characterized by autonomous aldosterone overproduction by the adrenal glands, affects 6% of the general hypertensive population and can be either sporadic or familial. Aldosterone producing adenoma (APA) and bilateral adrenal hyperplasia (BAH) are the two most frequent subtypes of sporadic PA, and 4 forms of familial hyperaldosteronism (FH-I to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Systematic review of the reported cases revealed that hypertension is present in 92.4% of the patients, hypokalemia (defined as serum K + <3.5 mmol/L) in 71.8% and hypoaldosteronemia (defined as serum aldosterone <5 ng/dL) in 58.2% of the cases. As reported for other forms of monogenic hypertension [ 89 , 90 ], this variability is not only observed between kindreds carrying different mutations, but also between affected members of the same family ( Table 1 ). It is likely that both environmental and genetic factors, including Na + intake and polymorphisms in genes involved in Na + handling could influence the phenotypic manifestation of the disease [ 63 ].…”
Section: Liddle Syndromesupporting
confidence: 69%
“…Systematic review of the reported cases revealed that hypertension is present in 92.4% of the patients, hypokalemia (defined as serum K + <3.5 mmol/L) in 71.8% and hypoaldosteronemia (defined as serum aldosterone <5 ng/dL) in 58.2% of the cases. As reported for other forms of monogenic hypertension [ 89 , 90 ], this variability is not only observed between kindreds carrying different mutations, but also between affected members of the same family ( Table 1 ). It is likely that both environmental and genetic factors, including Na + intake and polymorphisms in genes involved in Na + handling could influence the phenotypic manifestation of the disease [ 63 ].…”
Section: Liddle Syndromesupporting
confidence: 69%
“…The mechanisms leading to BHA remain poorly understood with the exception of the rare familial forms where germline mutations in CACNA1D, CACNA1H, KCNJ5 and CLCN2 have each been shown to cause bilateral adrenal aldosterone production [72][73][74]. The underlying causes of sporadic (non-familial) forms of CT-negative BHA often termed IHA still remain to be clarified.…”
Section: Apcc In Preclinical and Overt Primary Aldosteronismmentioning
confidence: 99%
“…However, despite this selection pressure not all predicted high confidence CACNA1D APA and APCC mutations may strongly contribute to disease risk because other, yet unknown mechanisms could be responsible. Notably, a substantial fraction of excessive aldosterone production in APAs is due to mechanisms not explained by somatic variants in known genes [24]. This emphasizes the need for further functional characterization of CACNA1D APA mutations to verify their causative roles.…”
Section: Introductionmentioning
confidence: 99%